2006
DOI: 10.1016/j.cell.2006.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Wnt Ligands Requires Evi, a Conserved Transmembrane Protein

Abstract: Wnt signaling pathways are important for multiple biological processes during development and disease. Wnt proteins are secreted factors that activate target-gene expression in both a short- and long-range manner. Currently, little is known about how Wnts are released from cells and which factors facilitate their secretion. Here, we identify a conserved multipass transmembrane protein, Evenness interrupted (Evi/Wls), through an RNAi survey for transmembrane proteins involved in Drosophila Wingless (Wg) signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
473
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 528 publications
(491 citation statements)
references
References 53 publications
13
473
2
3
Order By: Relevance
“…Evi is an essential component of the Wnt secretion machinery (Bänziger et al , 2006; Bartscherer et al , 2006; Goodman et al , 2006), and its protein levels are increased in cancer compared to normal colon tissue (Voloshanenko et al , 2013; Stewart et al , 2015). Since Evi must mediate the secretion of different Wnt proteins, it must be available as soon as any of the Wnt proteins is expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evi is an essential component of the Wnt secretion machinery (Bänziger et al , 2006; Bartscherer et al , 2006; Goodman et al , 2006), and its protein levels are increased in cancer compared to normal colon tissue (Voloshanenko et al , 2013; Stewart et al , 2015). Since Evi must mediate the secretion of different Wnt proteins, it must be available as soon as any of the Wnt proteins is expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen Wnt ligands are produced and subsequently processed in the endoplasmic reticulum (ER) by the attachment of palmitoleic acid to a conserved serine residue by the acyltransferase Porcupine (Porcn) (Kadowaki et al , 1996; Willert et al , 2003; Takada et al , 2006). In the Wnt secretory pathway, this lipid modification is important for the interaction between Wnt proteins and the conserved transmembrane protein Evi (Wls, GPR177), which shuttles lipid‐modified Wnt proteins to the plasma membrane and onto exovesicles (Bänziger et al , 2006; Bartscherer et al , 2006; Goodman et al , 2006; Gross et al , 2012; Herr & Basler, 2012). Evi is then recycled via the retromer complex back to the Golgi and ER (Coudreuse, 2006; Belenkaya et al , 2008; Franch‐Marro et al , 2008; Pan et al , 2008; Port et al , 2008; Yang et al , 2008; Yu et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies suggest that, in addition to regulating the transcription of the Wnt mRNA, pathway activity may be regulated at the level of ligand secretion. Studies performed on flies and worms have indicated that secretion of Wnts from the producing cells is regulated and that this level of regulation may be conserved in mammals [106][107][108]. Thus, mRNA expression, and even protein expression, do not equate to the production of active, secreted ligand.…”
Section: Summary and Future Of The Fieldmentioning
confidence: 99%
“…Une série d'articles publiés entre 2006 et 2008 par des équipes travaillant sur C. elegans, la drosophile et l'homme ont montré que la sécrétion du signal EGL-20/Wingless/ Wnt (différents noms d'un des WNT dans ces organismes respectifs) requiert l'intervention d'une protéine à plusieurs domaines transmembra naires conservée au cours de l'évolution jusqu'à l'homme et appelée Wntless/Evi/ Sprinter chez la drosophile [8][9][10] WNT est une glycolipoprotéine qui agit en qualité de molécule de signalisation dans de nombreux processus biologiques. WNT se distribue de façon graduée autour des cellules adjacentes aux cellules qui le produisent (en vert).…”
Section: Wntless Et Le Retromer Sont Requis Pour La Signalisation Wntunclassified
“…Dans les épithéliums de drosophile, certaines données suggèrent que WNT serait préférentiellement adressé au pôle apical [20], bien qu'un adressage au pôle basolatéral coexiste [20,21]. Dans les mutants Wntless, on trouve WNT dans toute l'épaisseur de la cellule [9]. Bien que ces résultats puissent indiquer que Wntless pourrait être requise pour la localisation apicale de WNT, ils pourraient tout aussi bien être secondaires à l'accumulation de WNT dans la cellule sécrétrice.…”
Section: Wntless Seulement Un Récepteur De Tri Pour Wnt ?unclassified